Kajian Etnosians Sarung Hitam Donggo Sebagai Nilai Budaya dan Sains Dalam Pembelajaran Ilmu Pengetahuan Alam di Sekolah Dasar - Sugmawati, Devia; Estiqomah (INOVASI, 2025)
Tembe Me'e, a traditional fabric from Donggo, is not only rich in aesthetic and cultural value but also incorporates scientific principles such as natural dyeing, crafting techniques, and physics concepts in its production process. Using an ethnoscience-based approach, this study integrates local wisdom into the science curriculum to enhance students' understanding of scientific concepts while strengthening cultural identity. The research aims to explore the potential of utilizing Tembe Me'e from Donggo as a source of cultural and scientific value in elementary school science education. A qualitative approach was employed, including interviews with a local weaver from Mbawa Village in Donggo and other community members. This method allowed the researchers to deeply understand the meanings and values embedded in Tembe Me'e as part of local cultural heritage. Additionally, a literature study was conducted by gathering various relevant references, such as textbooks, articles, and other resources. Based on interviews with the local weaver, Tembe Me'e is created through traditional processes that utilize natural materials, such as plant-based natural dyes. These processes include spinning, dyeing, and weaving techniques, which can be linked to concepts in natural sciences. The study also discovered that one of the techniques in making Tembe Me'e involves fermentation using parung leaves, which have been proven to help alleviate skin problems in humans. This indicates that discussions about parung leaves in the context of Tembe Me'e (traditional woven fabric) demonstrate that this herbal plant not only has benefits in traditional medicine but can also serve as relevant teaching material for natural science education at the elementary level. Thus, teachers can employ practical approaches, such as encouraging students to observe the leaves, understand their properties, or even practice traditional methods of their application.